ON THE PROBLEM OF THE GEOLOGICAL-TECTONIC STRUCTURE AND PLACEMENT OF THE APARAN SUITE (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article the geological-tectonic structure issue of the Middle Jurassic Aparan suite is discusses. Analyzing literary data, the author shows that in the geological maps and their sections the Aparan suite is not correctly represented: there are stratigraphic and structural disagreements and the geological-tectonic model presented by V. Agamalyan does not define the real situation. According to the author, the Aparan volcanic suite is a flyschoid monoclinic structure of the southeastern direction, which is by the stratigraphic unconformity overlying the rocks of the Precambrian metamorphic complex.
Keywords: geological-tectonic structure; Middle Jurassic volcanic flyschoid monoclinic structure; Precambrian metamorphic complex; stratigraphic unconformity